Lamentation is opposite: Abi Al-Tayyeb Al-Mutanabi and Abu Firas Al-Hamdani - Zayed, Enas Abdul Rahman (Al-Adab Journal, 2019)
These two poets - Abu al-Tayyib al-Mutanabi and Abu al-Firas al-Hamdani - have aroused my curiosity since the time of study. If we talk about one of them, we look at our side for the other, for they are the most important poets of the fourth century AH, the two stars of Saif al-Dawla’s council, and the most famous opponents of the artistic and literary arena.The strange thing is that many literary and critical studies neglected Abi Firas’s affairs, intentionally or without him, in order to focus on the other - al-Mutanabi - for explanation and detail.I liked to go through the experience of studying them together, because of their culture and literature, as well as their distinction of hating one another. When I examined their diwan, I found that it was full of various poetic purposes, and each had its own say in it, in addition to the fact that they innovated in one purpose and were short in the other for one reason or less. It exceeded all the stable purposes on one purpose that unites them, due to the lack of research and its lack of understanding for the rest of the purposes.